Screening of Maize Genotypes against Maize Weevil (Sitophilus zeamais Motsch.) in Laboratory Condition - Basyal, Kabita; Sapkota, Rekha; Tiwari, Kabita; Bhandari, Aashish (Journal of the Institute of Agriculture and Animal Science, 2022)
Maize (Zea mays) is the second-most important staple food crop in Nepal. However, it suffers from severe post-harvest losses. Maize weevil (Sitophilus zeamais Motschulsky) is one of the major storage pests of economic importance. Thus, an experiment was conducted in a Completely Randomized Design with three replications to screen 10 maize genotypes (Manakamana-4, Arun-4, Rampur Hybrid-4, CAH- 1715, Rampur Hybrid-6, Rampur Composite, Khumal Hybrid-2, Arun-2, Rampur Hybrid-10, and Poshilo Makai-1) against S. zeamais for tolerance and their effects on progeny emergence, grain damage, and weight loss in no-choice condition at National Entomology Research Centre, Khumaltar during November 2020 to May 2021 Among tested genotypes, least number of progeny emergence was observed in Rampur Composite (1.00) and Khumal Hybrid-2 (1.00) and highest was observed in Manakamana-4 (6.66) followed by Poshilo Makai-1 (3.00). The lowest percent grain damage was recorded in Khumal Hybrid-2 (1.03) followed by Rampur Hybrid-4 (1.28) and Rampur Composite (1.29) showing their tolerance to maize weevil. Similarly, the highest percent grain damage was recorded in the genotypes Manakamana-4 (6.57) and Poshilo Makai-1 (2.58) showing their susceptibility to maize weevil attack. The highest and lowest percent weight loss was recorded in Manakamana-4 (4.86) and Rampur Hybrid-4 (1.48) respectively. The other remaining genotypes were intermediate types. This finding is helpful to improve maize grain protection in storage and varietal improvement program.